2021
DOI: 10.1186/s13104-021-05471-5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection of human papillomavirus-16 among Sudanese patients diagnosed with squamous cell carcinoma and salivary gland carcinoma

Abstract: Objective Human papillomavirus (HPV) gained momentum as a potential etiological factor for many types of cancers. Therefore, the aim of this study was to assess the prevalence of HPV-16 infection among Sudanese patients diagnosed with Squamous Cell Carcinoma (SCC) and Salivary Gland Carcinoma. A descriptive, hospital-based study was conducted. 150 formalin-fixed paraffin-embedded blocks were collected. Results The study population included a total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…This might reflect the fact that the cyclin D1 is rarely amplified in HPV-infected tumors [51,52]. Although we do not have information on HPV infection on the studied samples, a previous study on Sudanese patients diagnosed with upper aerodigestive tract cancers showed 26 (17.3%) out of 150 patients were positive for HPV [53].…”
Section: Discussionmentioning
confidence: 81%
“…This might reflect the fact that the cyclin D1 is rarely amplified in HPV-infected tumors [51,52]. Although we do not have information on HPV infection on the studied samples, a previous study on Sudanese patients diagnosed with upper aerodigestive tract cancers showed 26 (17.3%) out of 150 patients were positive for HPV [53].…”
Section: Discussionmentioning
confidence: 81%
“…The Human Papillomavirus Genotyping Kit for 23 types (Yaneng Bioscience co., Shen Zhen, China) was used to perform PCR to amplify the conserved region of HPV gene in conjunction with reverse dot blot (RDB) analysis to identify the HPV subtypes. The membrane strips with fixed type-specific probes can detect infections from multiple HPV subtypes including 23 types (HPV 6,11,16,18,31,33,35,39,42,43,45,51,52,53,56,58,59,66,68,73,81,82,and 83). This method had a sensitivity of 104 copies/mL and a specificity of 99%; β-actin was used as an internal positive control (primer sequence of HPV18 E6E7 used in Table S2).…”
Section: Methodsmentioning
confidence: 99%
“… 18 Patients were seronegative for major viruses including HIV, Hepatitis E virus (HEV), human papillomavirus (HPV), and major human arboviruses such as chikungunya (CHIK), Crimean‐Congo hemorrhagic fever (CCHF), dengue (DEN), Rift Valley fever (RVF), West Nile (WNV), and Zika (ZIKV) viruses. 18 , 19 , 20 , 21 , 22 , 23 , 24 …”
Section: Introductionmentioning
confidence: 99%
“…18 Patients were seronegative for major viruses including HIV, Hepatitis E virus (HEV), human papillomavirus (HPV), and major human arboviruses such as chikungunya (CHIK), Crimean-Congo hemorrhagic fever (CCHF), dengue (DEN), Rift Valley fever (RVF), West Nile (WNV), and Zika (ZIKV) viruses. [18][19][20][21][22][23][24] Cases were presented at the outpatient clinic at the Royal Care hospital in Khartoum. Following the presentation of the first case an ethical approval was obtained from the research ethics committee (Institutional Review Board).…”
Section: Introductionmentioning
confidence: 99%